Persepsi Visual terhadap Dekorasi Fotografi Makanan di Imah Babaturan Bandung - Desintha, Siti (Program Studi Desain Interior Unikom, 2019)
Bandung is famous for a variety of unique and inexpensive culinary delights. This has become one of the attractions of tourism in addition to natural scenery such as the White Crater, Ranca Upas and so on. The growth of cafes is even more vibrant by offering a variety of interesting culinary. Imah Baturan is one food stall that has a home cooking concept. The interior of the room is made one with the food menu that is served. To reinforce the concept of home-based photography decoration there is a place to decorate it. Often at other eating places, the photographic element shown is more to appetizing food or 'beautiful' photos. Because one of the goals of food photography is visuals that can arouse the appetite so consumers are interested in tasting the food. But in the photo decor in Imah Babaturan, food photography displayed is far from a general definition. This research was conducted to determine the relation of denotation and connotation based on the construction of signs on the visual elements of photography, which are then analyzed to understand the meaning of the visualization. This research uses a qualitative method with the semiotic approach of Roland Barthes. Keywords: Food photography, visual perception, stalls.